Negotiating the Self during Delayed Graduation: An Intrapersonal Communication Perspective - Egidia Putri Sembiring Maha; Farikha Rachmawati (Lavish Opulent Education, 2026)
Delayed graduation among final-year students is not only an academic issue but also an internal experience that shapes how students understand themselves, manage pressure, and respond to their study completion process. This study aims to analyze the intrapersonal communication process of final-year students who experience delayed graduation at UPN Veteran Jawa Timur. This research applies a qualitative descriptive approach by using in-depth interviews with eight final-year students who had exceeded the ideal study period. The data were analyzed through reduction, data display, and conclusion drawing by focusing on the stages of intrapersonal communication, namely sensation, perception, memory, and thinking. The findings show that delayed graduation functions as a stimulus that triggers various emotional responses, including regret, anxiety, pessimism, sadness, and self-blame. These sensations develop into different self-perceptions, ranging from negative self-evaluation to reflective acceptance and stable self-perception when students attribute their delay to external factors. Memory also plays an important role in shaping students’ self-interpretation, as they connect current delays with past academic decisions, personal experiences, family responsibilities, psychological conditions, and institutional systems. The thinking process is mainly reflected through self-talk, which functions as a means of calming the self, strengthening motivation, expressing emotions, and directing future actions. This study concludes that intrapersonal communication among delayed final-year students is dynamic, subjective, and recursive. The implication of this study highlights the importance of academic and psychological support systems that consider students’ internal meaning-making processes, not only their academic progress.